Evaluation of the use of compensatory techniques in the Ribeirao do Santa Rita urban sub-basin in the municipality of Fernandopolis, Sao Paulo - Rodrigues, Gisele Carvalho [UNESP]; Santini Junior, Mauricio Antonio (Assoc Brasileira Engenharia Sanitaria Ambiental, 2021)
With the growth of the urban population and the consequent alteration of land use and occupation in the watersheds, floods have become more frequent. This paper aimed to verify the effects of the use of compensatory techniques in the watershed Ribeirao do Santa Rita, located in the city of Fernandopolis, Sao Paulo, Brazil. Peak flow and response time of various scenarios were analyzed in order to verify the potential for flood mitigation. The methodology used Storm Water Management Model (SWMM) to propagate the flow, with the support of the Geograph is Information Systems (GIS) to obtain the characteristics of the studied watersheed and the places of potential use of the techniques. The installation of several compensatory techniques was simulated, separately and together, for the 2017 urban configuration. Upon the hydrographs generated by each scenario, it was found that the best results occurred in events with shorter return time. Peak flow attenuation reached 33.72% using infiltration trenches, 31.38% for pours pavements, 31.08% using rain gardens, and 1220% with green roofs. The increase in lag time was up to 16 minutes. In the scenario with all compensatory techniques, the reduction in peak flow was up to 3729% and the response time increased by 18 minutes. Therefore, compensatory techniques can reduce peak flow and increase the response time of the sub-basin, consequently mitigating the occurrences of floods.
Keywords: urban hydrology; flood; low impact development; storm water management model